The Fabric of Airpower: Exploring the Foundations of Military Innovation - Byrnes, Michael. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisors: Robert Pfaltzgraff, and Richard Shultz.; Committee: Robert Pfaltzgraff, Richard Shultz, and David Blair.; Keywords: International relations, Military studies, and Political science.